[18F]Sodium fluoride PET-MRI detects increased metabolic bone response to whole-joint loading stress in osteoarthritic knees. Issue 11 (November 2022) - Watkins, L.E.; Haddock, B.; MacKay, J.W.; Baker, J.; Uhlrich, S.D.; Mazzoli, V.; Gold, G.E.; Kogan, F.
Summary: Objective: Altered joint function is a hallmark of osteoarthritis (OA). Imaging techniques for joint function are limited, but [ 18 F]sodium fluoride (NaF) PET-MRI may assess the acute joint response to loading stresses. [ 18 F]NaF PET-MRI was used to study the acute joint response to exercise in OA knees, and compare relationships between regions of increased uptake after loading and structural OA progression two years later. Methods: In this prospective study, 10 participants with knee OA (59 ± 8 years; 8 female) were scanned twice consecutively using a PET-MR system and performed a one-legged squat exercise between scans. Changes in tracer uptake measures in 9 bone regions were compared between knees that did and did not exercise with a mixed-effects model. Areas of focally large changes in uptake between scans (ROIfocal, ΔSUVmax > 3) were identified and the presence of structural MRI features was noted. Five participants returned two years later to assess structural change on MRI. Results: There was a significant increase in [ 18 F]NaF uptake in OA exercised knees (SUV P < 0.001, Ki P = 0.002, K1 P < 0.001) that differed by bone region. Conclusion: There were regional differences in the acute bone metabolic response to exercise and areas of focally large changes in the metabolic bone response that might be representative of whole-joint dysfunction.